Cinnamomum zeylanicum Essential Oil as an Antibacterial Agent and Dental Caries Prevention - Rizal, Moh. Basroni; Cevanti, Twi Agnita; Revianti, Syamsulina; Azmanu, Aulia Alam (Denta Journal Kedokteran Gigi, 2026)
Background: The prevalence of dental caries in Indonesia reaches 88.8%. Chlorhexidine, although effective, has side effects such as tooth discoloration. Cinnamomum zeylanicum is rich in cinnamaldehyde and eugenol, with antibacterial activity that makes it a natural alternative. Objective: To assess the effectiveness of Cinnamomum zeylanicum essential oil against Streptococcus mutans inoculated in Wistar rats (Rattus norvegicus) in preventing dental caries. Method: This study used 20 male Wistar rats, divided into five groups: negative control, positive control, and three treatment groups with Cinnamomum zeylanicum essential oil concentrations of 6.25%, 10%, and 12.5%. Streptococcus mutans (S. mutans) was inoculated orally in 0.2 ml using a pipette for three consecutive days. During the study, rats were fed a diet mixed with a sucrose solution (600 mg of sucrose dissolved in 1 liter of Aquadest) at a 1:500 ml-to-pellet ratio to induce caries. After 20 days of treatment, data were collected using a bacterial inhibitory zone assay by disk diffusion and salivary pH measurement. Data analysis was performed using one-way analysis of variance (ANOVA), Tamhane’s post-hoc test, and the Wilcoxon signed-rank test. Results: One-way ANOVA test showed no significant differences in the inhibitory zone (p>0.05). Post-hoc tests showed that all groups were not significant (p>0.05). The Wilcoxon signed-rank test showed significant differences in salivary pH before and after treatment (p<0.05). Conclusion: Cinnamomum zeylanicum essential oil has potential as an antibacterial agent and natural alternative in preventing dental caries against S. mutans, and is able to change the salivary pH to alkaline.